Inactivation of σ(F) in Clostridium acetobutylicum ATCC 824 Blocks Sporulation Prior to Asymmetric Division and Abolishes σ(E) and σ(G) Protein Expression but Does Not Block Solvent Formation - Jones, Shawn W. (American Society for Microbiology, 2011)

(untitled)
Clostridium acetobutylicum is both a model organism for the understanding of sporulation in solventogenic clostridia and its relationship to solvent formation and an industrial organism for anaerobic acetone-butanol-ethanol (ABE) fermentation. How solvent production is coupled to endospore formation—both stationary-phase events—remains incompletely understood at the molecular level. Specifically, it is unclear how sporulation-specific sigma factors affect solvent formation. Here the sigF gene in C. acetobutylicum was successfully disrupted and silenced. Not only σ(F) but also the sigma factors σ(E) and σ(G) were not detected in the sigF mutant (FKO1), and differentiation was stopped prior to asymmetric division. Since plasmid expression of the spoIIA operon (spoIIAA-spoIIAB-sigF) failed to complement FKO1, the operon was integrated into the FKO1 chromosome to generate strain FKO1-C. In FKO1-C, σ(F) expression was restored along with sporulation and σ(E) and σ(G) protein expression. Quantitative reverse transcription-PCR (RT-PCR) analysis of a select set of genes (csfB, gpr, spoIIP, sigG, lonB, and spoIIR) that could be controlled by σ(F), based on the Bacillus subtilis model, indicated that sigG may be under the control of σ(F), but spoIIR, an important activator of σ(E) in B. subtilis, is not, and neither are the rest of the genes investigated. FKO1 produced solvents at a level similar to that of the parent strain, but solvent levels were dependent on the physiological state of the inoculum. Finally, the complementation strain FKO1-C is the first reported instance of purposeful integration of multiple functional genes into a clostridial chromosome—here, the C. acetobutylicum chromosome—with the aim of altering cell metabolism and differentiation.